Egg monsters from Mars - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1996)
On an egg hunt, Dana finds an abnormal egg that is the size of a softball. It's covered with blue and purple veins and it's starting to hatch.
"An Apple paperback."
"A Parachute Press book."
Keywords: Horror tales